2016
DOI: 10.1111/psyp.12772
|View full text |Cite
|
Sign up to set email alerts
|

Pupillometry reveals changes in physiological arousal during a sustained listening task

Abstract: Hearing loss is associated with anecdotal reports of fatigue during periods of sustained listening. However, few studies have attempted to measure changes in arousal, as a potential marker of fatigue, over the course of a sustained listening task. The present study aimed to examine subjective, behavioral, and physiological indices of listening‐related fatigue. Twenty‐four normal‐hearing young adults performed a speech‐picture verification task in different signal‐to‐noise ratios (SNRs) while their pupil size w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
124
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(150 citation statements)
references
References 57 publications
10
124
0
Order By: Relevance
“…It is likely that in our study, the 579 steeper decrease of PPD in repeat-with-recall condition could also be the sign of 580 overload and fatigue with continuing effort to recognise, encode and rehearse isolated 581 words. However, the decreasing trend reported in McGarrigle et al[42] was not found 582 in McGarrigle et al[73] when using a similar test for school-aged children, so it is still 583 unclear how reliably and accurately this metric is related to fatigue.584Yet another possible explanation to the steeper decrease of PPD in 585…”
mentioning
confidence: 94%
“…It is likely that in our study, the 579 steeper decrease of PPD in repeat-with-recall condition could also be the sign of 580 overload and fatigue with continuing effort to recognise, encode and rehearse isolated 581 words. However, the decreasing trend reported in McGarrigle et al[42] was not found 582 in McGarrigle et al[73] when using a similar test for school-aged children, so it is still 583 unclear how reliably and accurately this metric is related to fatigue.584Yet another possible explanation to the steeper decrease of PPD in 585…”
mentioning
confidence: 94%
“…Cognitive and emotional processes evoke pupillary dilation in both humans and non-human primates, reflecting vigilance, arousal and attention (Laeng, Sirois & Gredebäck, 2012; Schneider M. et al, 2016; Becket Ebitz & Moore, 2017; McGarrigle et al, 2017; Foroughi, Sibley & Coyne, 2017). Hence, pupillary diameters may serve as an index of brain activity and mental efforts (or lack hereof).…”
Section: Discussionmentioning
confidence: 99%
“…A device that offers large effort benefits and modest intelligibility benefits could greatly improve communication for individuals for whom recognizing speech in noisy environments can be difficult and often exhausting (Gosselin & Gagné, 2011;Tun, McCoy, & Wingfield, 2009;Wingfield et al, 2005) . Because listening to speech in real-world settings rarely occurs in isolation, decreases in listening effort can have important consequences for listeners and may be expected to improve users' ability to multitask, recall what they heard (e.g., see Sommers & Phelps, 2016;Van Engen, Chandrasekaran, & Smiljanic, 2012) , or reduce fatigue (Alhanbali, Dawes, Lloyd, & Munro, 2017;McGarrigle, Dawes, Stewart, Kuchinsky, & Munro, 2016;McGarrigle et al, 2014) .…”
Section: Discussionmentioning
confidence: 99%